2021
DOI: 10.1016/j.ekir.2020.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Grip Strength in Adults and Children with Cystinosis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Additionally, in another study, according to the degree of CKD, there were differences in the HGS z-score, which found those with stage 2-5 CKD had a lower HGS z-score than those with stage 1 CKD [59]. HGS is a reliable bedside tool for nutritional assessments in children with CKD [55,59,60].…”
Section: Feasibility and Accuracy Of Hgs In Detection Mwd Among Hospi...mentioning
confidence: 94%
See 3 more Smart Citations
“…Additionally, in another study, according to the degree of CKD, there were differences in the HGS z-score, which found those with stage 2-5 CKD had a lower HGS z-score than those with stage 1 CKD [59]. HGS is a reliable bedside tool for nutritional assessments in children with CKD [55,59,60].…”
Section: Feasibility and Accuracy Of Hgs In Detection Mwd Among Hospi...mentioning
confidence: 94%
“…HGS z-scores are used in children with CKD to assess muscle strength and detect MWD. For example, a cohort study assessing muscle strength found that HGS z-scores in children suffering from CKD with cystinosis were lower than those in children with CKD without cystinosis [55]. Additionally, in another study, according to the degree of CKD, there were differences in the HGS z-score, which found those with stage 2-5 CKD had a lower HGS z-score than those with stage 1 CKD [59].…”
Section: Feasibility and Accuracy Of Hgs In Detection Mwd Among Hospi...mentioning
confidence: 98%
See 2 more Smart Citations
“…Later, patients show pronounced distal weakness, more so than proximal weakness and contractures [ 35 ]. A recent study in 76 pediatric and adult INC patients showed a mean grip strength SD-score of −2.1, which was significantly lower compared to CKD patients with other underlying kidney diseases [ 39 ]. Reduced grip strength was associated with the male gender, delayed cysteamine therapy, and low levels of physical activity.…”
Section: Cystinosis Metabolic Bone Diseasementioning
confidence: 99%